Tropospheric Ozone Alters the Chemical Signal Emitted by an Emblematic Plant of the Mediterranean Region: The True Lavender (Lavandula angustifolia Mill.) - Dubuisson, Candice; Nicolè, Florence; Buatois, Bruno; Hossaert-McKey, Martine; Proffit, Magali (Frontiers in Ecology and Evolution, 2022)
Among air pollutants, tropospheric ozone (O3) is one of the most stressful for organisms due to its strong oxidative potential. For instance, high ozone concentration ([O3]) has the potential to affect (i) the emission of volatile organic compounds (VOCs) by plants and (ii) the lifetime of these VOCs in the atmosphere, and consequently disturb crucial signals in the interactions between plants and other organisms. However, despite the determinant role of VOCs emitted by flowers for pollinator attraction, a very limited number of studies have investigated the impact of O3 on floral VOCs. In this study, we investigated the effect of high [O3] episodes on the VOCs emitted by a flowering Mediterranean plant: the true lavender (Lavandula angustifolia Mill., Lamiaceae). To do so, in controlled conditions, we exposed (i) the entire plant to high but realistic [O3] (200 ppb for 5 h) and (ii) only the VOCs emitted by lavender to increasing [O3] (0, 40, 80, 120 and 200 ppb). We sampled VOCs of lavender in both conditions and analysed them by Gas Chromatography-Mass Spectrometry in order to qualify and quantify the flowering lavender’s emissions and the reaction of VOCs with O3 in the atmosphere. Our results showed that exposure to high [O3] during a short period (5 h) did not affect the emission of VOCs by flowering lavender. Incidentally, we also showed that the chemical signal varied in quantities and proportions over the day. Moreover, we showed that after their emission by the plant, composition of the VOCs changed quantitatively and qualitatively in an atmosphere containing [O3] naturally observed nowadays.Quantities of several of the major terpenes emitted by lavender decreased drastically during O3 exposure, whereas concentrations of some VOCs increased, such as carbonyls and carboxylic acids, which are probably reaction products of terpenes with O3. Exposure to high [O3] thus directly affected the proportions of VOCs in the atmosphere. Because pollinators generally use a blend of VOCs in particular proportions as a signal to localize flowers, the numerous pollinators of lavender may experience difficulty in recognizing specific floral odors during frequent and moderate [O3] episodes in the Mediterranean region.